PERAN MASJID DALAM PERUBAHAN SOSIAL STUDI KASUS AKSI 212, FENOMENA ERDOGAN DAN MASJID JOGOKARYAN YOGYAKARTA - Mulyanto Abdullah Khoir (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
The purpose of this study is to find out about the role and function of mosques in social change, a case study of the 212 Islamic Defense Action, the Erdogan Phenomenon and the Yogyakarta Jogokaryan Mosque, as well as the influence and correlation of these three cases in social change. Including qualitative research which intends to understand the phenomena experienced by research subjects such as behavior, perceptions, motivations, actions, and others holistically by describing the various objects. Using a case study approach, namely the status of the research subject with respect to a specific or typical phase of the whole personality. The results of the study, historically fact, both during the time of the Rasulullah SAW and after it, the mosque has an important role in social change, where the mosque as a agent of change. In the context of the 212 Islamic Defense Action, the mosque was used as the basis of the movement. In the case of the Erdogan Phenomenon, the mosque which was previously used as a means of worship for mahdhah was returned to its function as a means of worship, communication and various social interactions in order to solve various problems that occur in society. Meanwhile, in the case of the Jogokaryan mosque in Yogyakarta, the mosque provides services and empowers the various needs of the community. These three cases have an impact on changes that occur in the structure and function of society. Changes in social relationships or changes in the balance (equilibrium) of social relationships. Defending Islam 212 is identified as the basis for social change, Erdogan as the basis for political change and the Jogokaryan Mosque as the basis for economic change. Both these social, political and economic changes have the same basis, namely the mosque as a magnet of change (center of gravity).